TREATMENT OF PATIENTS WITH HEART DISEASES WITH FUNCTIONAL FOODS - Tojiddinov Husniddin Saloxiddinovich (Galaxy International Interdisciplinary Research Journal, 2022)
Among non-drug methods of prevention and treatment of cardiovascular diseases, therapeutic nutrition is of great importance. Hypercholesterolemia is one of the main risk factors for the development of atherosclerosis and other heart and vascular diseases.